(untitled) (Journal of Medical & Health Sciences Review, 2025)
Musculoskeletal disorders (MSDs) area leading occupational health concern globally, especially among personnel in physically demanding jobs. Traffic police in Kohat are consistently exposed to prolonged standing, awkward postures, and repetitive movements, increasing their susceptibility to MSDs, which in turn may significantly impair their quality of life (QoL). This study aimed to assess the prevalence of MSDs among traffic police officers in Kohat, identify associated risk factors, and evaluate the impact of these disorders on their quality of life. A descriptive cross-sectional study was conducted with 218 male traffic police personnel aged 20–50 years, using convenience sampling. Data were collected using validated instruments: the Nordic Musculoskeletal Questionnaire (NMQ), Numerical Pain Rating Scale, Physical Activity Risk Factor and Quality of Life Assessment Questionnaire. Statistical analysis was performed using SPSS v27, applying chi-square tests and descriptive statistics. The study found that 88.1% of participants experienced moderate MSDs, with the lower back (21.1%), shoulders (14.7%), and neck (12.8%) being the most affected regions. Moderate QoL impairment was reported by 85.8%of the sample. Significant associations were found between age and MSD severity (p = 0.042), pain duration and MSD severity (p = 0.010), and duration of service and pain intensity (p < 0.001). Physical activity risk increased with both age and service duration, indicating cumulative ergonomic stress. MSDs are highly prevalent among traffic police in Kohat and significantly affect their physical health and QoL. Risk increases with age, years of service, and prolonged pain duration. The findings underscore the need for early ergonomic interventions, routine health screenings, and policy reforms to mitigate occupational risks and enhance the well-being of traffic police personnel.